Institutionalizing Neutrally Competent Policy Analysis: Resources for Promoting Objectivity and Balance in Consolidating Democracies - Weimer, David L. (My University, 2004)
The creation of institutions that foster objective policy analysis can be eased if the organizations emphasize resources that include reputations of neutral competence, independence, use of professional norms, participation in international organizations and transparency. This essay outlines the logic  of designing institutions based on these resources, illustrates their use and speculates on applying them in consolidating democracies.